2009
DOI: 10.1093/nar/gkn905
|View full text |Cite
|
Sign up to set email alerts
|

Update of the Diatom EST Database: a new tool for digital transcriptomics

Abstract: The Diatom Expressed Sequence Tag (EST) Database was constructed to provide integral access to ESTs from these ecologically and evolutionarily interesting microalgae. It has now been updated with 130 000 Phaeodactylum tricornutum ESTs from 16 cDNA libraries and 77 000 Thalassiosira pseudonana ESTs from seven libraries, derived from cells grown in different nutrient and stress regimes. The updated relational database incorporates results from statistical analyses such as log-likelihood ratios and hierarchical c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
50
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(52 citation statements)
references
References 32 publications
1
50
1
Order By: Relevance
“…Thus, we can conclude that RedCAP and LHCF2 show a diurnal regulation of the gene expression at LL, which is not maintained in D or under ML illumination. This is in agreement with previous studies showing diurnal regulation of LHCF2 genes [36,38] and with the clustering of the P. tricornutum RedCAP gene with LHCF and LHCF-like genes in a hierarchical clustering analysis of diatom ESTs obtained from a range of different environmental conditions [39]. …”
Section: Resultssupporting
confidence: 93%
“…Thus, we can conclude that RedCAP and LHCF2 show a diurnal regulation of the gene expression at LL, which is not maintained in D or under ML illumination. This is in agreement with previous studies showing diurnal regulation of LHCF2 genes [36,38] and with the clustering of the P. tricornutum RedCAP gene with LHCF and LHCF-like genes in a hierarchical clustering analysis of diatom ESTs obtained from a range of different environmental conditions [39]. …”
Section: Resultssupporting
confidence: 93%
“…We also observed that methylation in the promoter (upstream 500 bp) of genes does not appear to impact transcription levels. We had previously estimated the degree of differential expression of P. tricornutum genes across 16 complementary DNA (cDNA) libraries by calculating the statistical significance of differential mRNA levels in specific conditions compared with random distribution (log likelihood ratio, R-value) 25,28 . Considering these criteria, constitutively expressed genes have low R-values (o12) while genes that are significantly overrepresented in specific growth conditions have high R-values (412).…”
Section: Resultsmentioning
confidence: 99%
“…Studies in diatoms have benefited from developments in two model species, the centric diatom T. pseudonana (Coscinodiscophyceae) and the pennate diatom Phaeodactylum tricornutum (Bacillariophyceae), for which intense efforts have resulted in fully sequenced genomes (Armbrust et al, 2004;Bowler et al, 2008) and provided reference data for transcriptomic (Maheswari et al, , 2009Allen et al, 2008;Sapriel et al, 2009;Shrestha et al, 2012;Chauton et al, 2013) and whole-cell proteomic Nunn et al, 2009) analyses. P. tricornutum is pleiomorphic, with three major morphotypes (fusiform, triradiate, and oval).…”
mentioning
confidence: 99%